Properties of Biodegradable Polymer from Terrestrial Mushroom for Potential Enhanced Oil Recovery - Tengku Amran Tengku Mohd; Shareena Fairuz Abdul Manaf; Munawirah Abd Naim; Muhammad Shafiq Mat Shayuti; Mohd Zaidi Jaafar (Universitas Gadjah Mada, 2020)
Polymer flooding could enhance the oil recovery by increasing the viscosity of water, thus, improving the mobility control and sweep efficiency. It is essential to explore natural sources of polymer, which is biologically degradable and negligible to environmental risks. This research aims to produce a biodegradable polymer from terrestrial mushroom, analyze the properties of the polymer and investigate the oil recovery from polymer flooding. Polysaccharide biopolymer was extracted from mushroom and characterized using Fourier Transform Infrared Spectrometer (FTIR), while the polymer viscosity was investigated using an automated microviscometer. The oil recovery tests were conducted at room temperature using a sand pack model. It was found that polymer viscosity increases with increasing polymer concentration and decreases when increase in temperature, salinity, and concentration of divalent ions. The oil recovery tests showed that a higher polymer concentration of 3000 ppm had recovered more oil with an incremental recovery of 25.8% after waterflooding, while a polymer concentration of 1500 pm obtained incremental 22.2% recovery of original oil in place (OOIP). The oil recovery from waterflooding was approximately 25.4 and 24.2% of the OOIP, respectively. Therefore, an environmentally friendly biopolymer was successfully extracted, which is potential for enhanced oil recovery (EOR) application, but it will lose its viscosity performance at certain reservoir conditions.